Breast milk nutrient content and infancy growth. (6th April 2016) - Prentice, Philippa; Ong, Ken K.; Schoemaker, Marieke H.; van Tol, Eric A. F.; Vervoort, Jacques; Hughes, Ieuan A.; Acerini, Carlo L.; Dunger, David B.
Abstract: Aim: Benefits of human breast milk (HM) in avoiding rapid infancy weight gain and later obesity could relate to its nutrient content. We tested the hypothesis that differential HM total calorie content (TCC) or macronutrient contents may be associated with infancy growth. Methods: HM hindmilk samples were collected at ages 4–8 weeks from 614 mothers participating in a representative birth cohort, with repeated infancy anthropometry. HM triglyceride (fat), lipid analytes and lactose (carbohydrate) were measured by 1 H‐NMR, and protein content by the Dumas method. TCC and %macronutrients were determined. Results: In 614 HM samples, fat content was as follows: [median(IQR)]: 2.6 (1.7–3.6) g/100 mL, carbohydrate: 8.6 (8.2–8.8) g/100 mL, protein: 1.2 (1.1–1.2) g/100 mL; TCC: 61.8 (53.7–71.3) kcal/100 mL. HM of mothers exclusively breast feeding vs. mixed feeding was more calorific with higher %fat, lower %carbohydrate and lower %protein. Higher HM TCC was associated with lower 12‐months body mass index (BMI)/adiposity, and lower 3–12 months gains in weight/BMI. HM %fat was inversely related to 3–12 months gains in weight, BMI and adiposity, whereas %carbohydrate was positively related to these measures. HM %protein was positively related to 12‐months BMI. Conclusion: HM analysis showed wide variation in %macronutrients. Although data on milk intakes were unavailable, our findings suggest functional relevance of HM milk composition to infant growth. Abstract :